Intimate Diversity : An Anglican Practical Theology of Interreligious Marriage - Smith, Paul Aidan, (Theology and Mission in World Christianity ;, 2021)
In Intimate Diversity Paul Smith explores theological implications of interreligious marriage. Taking a practical theology approach which begins with lived experience and works through a pastoral cycle involving interpretation, normative discussion and a pragmatic outcome, the book challenges the Church of England (or other denominations) fulfil three tasks: theological, pastoral and missional. Paul Smith accepts the reality of marriage that involves couples from different religious traditions and proposes ways of justifying such marriage based on normative Christian traditions. He takes a broadly missional approach, advocating the positive role that the Church of England can play in fostering good interreligious relations in society whilst offering sympathetic pastoral support of couples who marry across religious divides.